Methicillin-resistant Staphylococcus aureusmenace: A dermatologist's perspective - Manjunath Hulmani; Shruti Kakar; V Jagannath Kumar (Wolters Kluwer Medknow Publications, 2017)
Staphylococcus aureus is a facultative anaerobic, Gram-positive coccal bacterium. In contemporary times, one of the major concerns in all fields of medicine is the emerging resistance to S. aureus. There are two types of methicillin-resistant S. aureus (MRSA), that is, hospital acquired (HA) and community acquired (CA). HA-MRSA strains contain staphylococcal cassette chromosome mec (SCCmec) I and II, which are larger and have the capacity for multidrug resistance. High expression of Panton-Valentine leukocidin (PVL), phenol-soluble modulins (PSM), α-toxin, core genome-encoded superantigen SEIX, and teichoic acid contributes to increased virulence in CA-MRSA strains. Methicillin resistance in staphylococci is due to the acquisition of a mobile genetic element (mec) called the SCCmec. All SCCmec types include the mecA gene, which codes for the low-affinity penicillin-binding protein (PBP) 2a. Resistance is due to the fact that β-lactam antibiotics cannot inhibit PBP2a. Biofilms are surface-attached bacterial agglomerations embedded in extracellular matrix. There are various toxins such as PVL, PSMs, surface-anchored S. aureus-binding proteins, and SasX protein. It can cause folliculitis, furunculosis, abscesses, carbuncles, cellulitis, necrotizing pneumonia, urinary tract infection, osteomyelitis, septic arthritis, thrombophlebitis, endocarditis, and toxic shock syndrome. Many diagnostic modalities are available to identify MRSA. The mainstay of treatment is incision and drainage. Systemic antibiotics such as clindamycin, doxycycline, trimethoprim-sulfamethoxazole, linezolid, daptomycin, tigecycline, and tedizolid are the most commonly used antibiotics. The prevalence of CA-MRSA is on the rise, and as a dermatologist, our concern is to prevent the occurrence of recurrent furunculosis and patient dissatisfaction.